Epistemologies of fire: an approach from ancestral thoughts - Sánchez Riaño, Federico; Mora, Aura Isabel (Derecho y Realidad, 2019)
This article reveals an investigation carried out on the production of ancestral thoughts from the rituals of many native populations of America (Abya Yala) in what has been called by the authors “Epistemologies of fire”. Here their ways of production, search and transmission of knowledge are set which, from the ancestral, have been used by indigenous communities for the construction of a community, privileging how each being thinks of itself inside a world view and a cosmic intelligence1 that allows for bases to be laid to confront the idea of internal and external separation, that has been pursued by human beings since the western construction of the world. Continuing with the idea elaborated by other authors of a pluriverse (a world where many worlds can fit), these epistemologies based in the recognition of diversity contribute as well to the construction of an academic polyphony that can recapture these native sciences to integrate their knowledge and the way of producing them to expand the perspectives in Social Sciences. Continuing with the idea woven by other authors of a pluriverse (a world where many worlds fit), these epistemologies based on the recognition of diversity also contribute to the construction of an academic polyphony that can take up these native sciences to integrate their knowledge and way to produce them to broaden the perspectives in the Social Sciences. An immersion work was developed using learning and description methodologies specific to the villages with which the work was carried out. This allowed us to carry out an exercise in careful listening to the spoken word of the elderly (knowledgeable grandparents) and participation in their rituals, which are understood as ancestral pedagogies.